TINJAUAN HISTORIS PERKEMBANGAN PENDIDIKAN DAN KEKRISTENAN DI AMBOINA 1607 -1864 - Belly Isayoga Kristyowidi (TANGKOLEH PUTAI, 2019)
This paper aims to explore the relationship between the presence of Western nations, especially since the Company era (VOC) to the Dutch East Indies colonialism with the development of education and Christianity in Amboina (Ambon) in the period 1607-1864. Through the historical method to parse and analyze every event in the dimensions of space and time using historical research principles, the historical method has stages from heuristics, verification (criticism), interpretation to historiography. Various efforts were made to improve the condition of education in Amboina, including by utilizing pastors as well as becoming a schoolmeester. Through education, the Company wanted to replace the existing religion. Thus, this education policy is a mixture of religious interests and political economy. The presence of Zending in this case also advances education in Amboina, various ways are continuously carried out to improve the state of education and Christianity and to meet skilled indigenous educators who are willing to be placed anywhere by the government. By conducting blusukan and establishing schools and institutes to formulate curricula, education for natives can be a driving force for establishing Christianity in Amboina. In view of its development, education is a way of Christianity which is the embodiment of Culus Region Eius Religio.